Lapsas tēls un tā ietekme uz japāņu folkloru - Akhmedova, Darya (Latvijas Universitāte, 2021)
Japan is and has been for thousands of years a very spiritual nation that is influenced by three different religions as well as folklore and myth. The three main religions in Japan being Shintoism, Buddhism, and Confucianism, all three offer its followers different moral perspectives that in Japan meld with each other and the folklore that is dominated by strange creatures and horrific monsters. Japanese folklore is also populated by real animals that have been given special abilities and powers which make them a part of the supernatural world. The yōkai, which are a great example of folklore, are made up of demons, shapeshifters, spirits, and all other sorts of various creatures. Like many myths from Europe and the Americas some of these supernatural creatures including yōkai have a real world animal equivalent. Yōkai are not only creatures, but can be gods as well. They appear in folktales, myths and legends much the same as werewolves, witches and vampires do in Europe. During the Edo period the stories and legends would have been one of the main ways people knew about or were connected to these creatures because the period was marked by a decrease in religious activity. That is not to say that Shintoism, Buddhism, and Confucianism were not present in Japanese society during this time but there was no state enforcement of religion, but the Edo government did require "all Japanese to be registered members of some recognized Buddhist sect." Religion offers answers to many of life’s questions, in Japan however it was not only religion that offered answers to world events, yōkai do as well. The fox has an interesting and complex place in Japanese folklore and legend, it became associated with the God of Rice, Inari in the 11th century. After this many of the evil doings of the fox can be attributed to this connection. The fox is an incredibly powerful creature that not only can transform itself but, "They have the power of infinite vision; they can hear everything and understand the secret thoughts of mankind generally." Japanese myth and legends have been told for centuries and were used to teach moral and life lessons. They explain the world through supernatural means and entertainment. These tales reveal a world full of supernatural creatures and monsters that terrorize the world we call reality. This reality is challenged by the one who is exposed to myths and legends. These myths and their reality allow for moral and life lessons to be taught in an entertaining way which lends itself to their retelling before and after they were first written down in The Kojiki in 712 CE. Thesis’s main text consists of 50 pages.
Image of Fox and Its Influence on Japanese Folklore
Keywords: Āzijas studijas; Kitsune; Magical fox; Yokai; Japanese myths